(3cJGH ehGRjf GdGMLGQ Ydi QCi HdjfGSs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GUWai eMeO CeG HYO aEfg bO JbOe bHd cJGHfG gPG GYOI cJH ai Yde GdehGRjf hdeG cGf HdjfGS bO NGdafG ai HYV GdaQhY s
(3BNQgG (B:s
(3agh JQJjH Gdbhd ai JCOjI HQgGf GdNHQ Cf JQJjH gPg GdGYeGd hGdJYdje Je GdLRA GdKGfi ef cJGH GdGMLGQ Ydi QCi HdjfGS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs